ABOUT THE EXACT SOLUTION IN TWO PHASE-STEFAN PROBLEM - Boucíguez, A. C.; Lozano, R. F.; Lara, M. A. (Revista de Engenharia Térmica, 2007)
Two cases of the two - phase Stefan problem in a semi - infinite slab are presented here: one has heat flux boundary condition proportional to t−½ and the other has constant temperature boundary condition. In these two cases the exact solution exists, the relationship between the two boundary conditions is presented here, and the equivalence between the two problems is shown.